METODE PEMBELAJARAN HADITS DI MASA NABI MUHAMMAD - Abdullah Ali Ridho; Syaiful Hadi (As-Sulthan Journal of Education, 2025)
The method of learning hadith during the time of the Prophet Muhammad had many challenges. In addition to him himself forbidding his companions in general to write down the hadith he conveyed, at that time there was no other method to store knowledge other than memorizing it. Although only the memorization method was left to keep knowledge from being lost, the Prophet Muhammad used various methods so that his companions could easily memorize and understand the learning he conveyed. This study aims to comprehensively examine the concept of hadith learning during the time of the Prophet Muhammad, starting from the methods used to the supporting methods. The study was conducted using a library research approach. Data were collected through books related to this. The results of the study indicate that the memorization method remains relevant anytime and anywhere and is able to face the challenges of the times.